Seroprevalence of Toxocara antibodies in patients with adult asthma - Kuk, Salih; Ozel, Eda; Oguzturk, Hakan; Kirkil, Gamze; Kaplan, Mustafa (Lippincott Williams & Wilkins, 2006)
Toxocariasis is a common worldwide infection. Asthma, considered to be one of the most common chronic diseases, is a serious global health problem. Toxocara may be a possible etiologic agent of asthma. The aim of this study was to investigate whether there is an association between adult asthma and Toxocara sero-prevalence. Fifty three adult patients with asthma participated in the study. All patients had an age of disease onset of 20 years or older. Blood samples were tested for the presence of Toxocara antibodies using enzyme-linked immunosorbent assay (ELISA). We found a 13.2% Toxocara seropositivity for asthma. There was a significant difference in the Toxocara seropositivity between adult asthma patients and our healthy cohort populations. There was no significant difference between Toxocara seropositive asthma and Toxocara seronegative asthma in terms of the risk factors for Toxocara infection. We believe that further research with a large number of asthma patients is warranted and preventive strategies in this patient population are needed.
Keywords: Toxocara; adult asthma; Turkey